Thioester derivatives of the natural product psammaplin A as potent histone deacetylase inhibitors - Baud, Matthias G. J.; Leiser, Thomas; Petrucci, Vanessa; Gunaratnam, Mekala; Neidle, Stephen; Meyer-Almes, Franz-Josef; Fuchter, Matthew J. (Beilstein Journal of Organic Chemistry, 2013)
There has been significant interest in the bioactivity of the natural product psammaplin A, most recently as a potent and isoform selective HDAC inhibitor. Here we report our preliminary studies on thioester HDAC inhibitors derived from the active monomeric (thiol) form of psammaplin A, as a means to improve compound delivery into cells. We have discovered that such compounds exhibit both potent cytotoxicity and enzymatic inhibitory activity against recombinant HDAC1. The latter effect is surprising since previous SAR suggested that modification of the thiol functionality should detrimentally affect HDAC potency. We therefore also report our preliminary studies on the mechanism of action of this observed effect.
Keywords: epigenetics; histone deacetylase; natural product; prodrug; psammaplin A; thioester